Highly pathogenic and multidrug resistant avian pathogenic escherichia coli in free-range chickens from Brazil - Oliveira, E. S. [UNESP]; Cardozo, M. V. [UNESP]; Borzi, Mariana Monezi [UNESP]; Borges, C. A. [UNESP]; Guastalli, E. A.L.; Ávila, F. A. [UNESP] (FapUNIFESP (SciELO), 2019)
Avian pathogenic Escherichiacoli (APEC) virulence mechanism has been continuously studied and it is believed to be multifactorial and because of this, this work aimed to characterize potentially APEC strains isolated from free-range hens. Isolates were submitted to PCR for the detection of virulence genes, which were of high prevalence. In vivo inoculation of day-old chicks revealed that 49 of these strains were of high and intermediate pathogenicity. In addition, isolates were submitted to antimicrobials susceptibility test with the majority of the strains presenting multiresistance. Phylogenetic analysis showed a greater presence of potentially APEC isolates in-group B2. In addition, high heterogeneity was detected among the isolates byXbaI enzyme. Fifteen serogroups were identified, being the O8 the most frequent. These results strengthen the fact that a combination of diverse factors are associated with the pathogenicity APEC strains, as well as to highlight its importance to public health and that free-range hens can act as a reservoirs of potentially zoonoticbacteria.
Keywords: APEC; Backyard chickens; Colibacillosis; Pathogenicity; Virulence factors